THE RELATIONSHIP OF HUSBAND'S SUPPORT AND BOUNDING ATTACHMENT WITH THE RISK OF POSTPARTUM BLUES IN POSTPARTUM S ECTIO CAESAREA MOTHERS IN THE SAKURA ROOM OF DR. SOEDOMO TRENGGALEK - Windayati, Della Rahma; Pertami, Sumirah Budi; Solikhah, Fitriana Kurniasari; Kasiati, Kasiati (Indonesian Journal of Applied Health, 2024)
After giving birth, women will go through postpartum psychological changes which are divided into 3, namely taking in, taking hold, and letting go. If postpartum psychological changes cannot be overcome properly, it can cause postpartum blues. The changes that occur require the husband's support and the success of bonding attachment in preventing failure to get through the postpartum period, thereby preventing the emergence of postpartum blues. The aim of this study was to determine the relationship between husband's support and bounding attachment with the risk of postpartum blues in postpartum caesarean section mothers. This research design uses cross sectional. The sampling technique used was non-probability sampling, purposive sampling type with a total of 59. Data processing uses the SPSS application with the Spearman-Rank test and Multiple Correlation. The research results showed a relationship between husband's support and the risk of postpartum blues with a p-value = 0.000. There is a relationship between bounding attachment and the risk of postpartum blues with a p-value = 0.000, and there is a relationship between husband's support and bounding attachment with the risk of postpartum blues simultaneously with a p-value = 0.000. It is recommended that postpartum mothers, especially caesarean sections, can adapt during the postpartum period and changes in new roles by increasing bounding attachment, and it is also recommended that husbands increase their support to wife so that they can prevent the risk of postpartum blues.